Numerical study of laminar nacelles: natural and hybrid laminar flow designs. (1st January 2014) - Vermeersch, O.; Bouteiller, Xavier
This paper presents the numerical design of laminar nacelle engine. Both natural laminar flow and hybrid laminar flow control strategies that have been used to achieve laminar nacelle will be described. Numerical process is based on Euler computations coupled with boundary layer stability analyses. Influence of parameters acting on transition such as mean flow distortion (due to the pylon or wall suction), surface imperfections and wall heating will be analysed.